2022
DOI: 10.20527/quantum.v13i1.12109
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Model Problem Based Learning Berbasis Stem Dengan Media Virtual Reality Terhadap Kemampuan Berpikir Kritis Dan Self Regulation Peserta Didik

Abstract: Telah dilakukan penelitian tentang implementasi model PBL berbasis STEM dengan media virtual reality terhadap kemampuan berpikir kritis dan self regulation peserta didik pada materi sistem koloid. Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan berpikir kritis dan self-regulation terhadap implementasi model PBL berbasis STEM dengan media virtual reality. Metode yang digunakan adalah pre-experiment dengan one group pretest-posttest design. Sampel penelitian adalah peserta didik kelas XI MIPA 1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Research supports this approach, as it has been shown that students' critical thinking skills improve significantly through teaching and learning activities that involve manipulating objects in a virtual world that is similar to the real world [12]. Other research supports the idea that the use of virtual reality in the learning process can significantly enhance students' critical thinking skills [13]. Another component that can be integrated into the process of improving critical thinking skills is ethnomathematics, specifically Javanese cultural nuances.…”
Section: Introductionmentioning
confidence: 97%
“…Research supports this approach, as it has been shown that students' critical thinking skills improve significantly through teaching and learning activities that involve manipulating objects in a virtual world that is similar to the real world [12]. Other research supports the idea that the use of virtual reality in the learning process can significantly enhance students' critical thinking skills [13]. Another component that can be integrated into the process of improving critical thinking skills is ethnomathematics, specifically Javanese cultural nuances.…”
Section: Introductionmentioning
confidence: 97%
“…Indigosol dye is a mixed batik dye between indigo and sodium nitrite (NaNO2 ) which uses HCl as a lock. Remazol dyes are dyes whose application process uses a dab technique (such as painting, using a brush) with a color lock in the form of waterglass (Na 2 (SiO 2 )/sodium silicate (Arifah et al, 2022;Muna Lia et al, 2016;Syafei, 2016) The dyes in batik are closely related to chemical bonding material, but the mastery of the concept of the material is still relatively low, and the learning media is not yet supportive, so students find it difficult to understand (Art et al, 2019;Fiteriani et al, 2021;Khairunnisa et al, 2022;Klasik et al, n.d.;Shanti, 2016;Triwidyati & Hadiyati, 2020). Students cannot distinguish between covalent bonds and ionic bonds.…”
Section: ▪ Introductionmentioning
confidence: 99%